"Franklin H. Knower (1901–1993)—a model for communicology": edited reprint with an introduction by Richard L. Lanigan. Issue 4 (2nd October 2018) - Lanigan, Richard L.
ABSTRACT: The foundation of disciplines is often associated with initial books and their authors. The discipline of speech–communication–communicology is no exception. Books by Albert Craig Baird, Lester Thonssen, and Franklin Hayward Knower serve as the definition of our early discipline. This article is about foresight—the anticipation of future developments for what was initially called "general speech, " whose practitioners have ever since been known as generalists. Departments and schools of communicology are now emerging worldwide as a synthesis of problematics and thematics that used to be called general speech. Knower suggested in 1962 that the beginning of theoretical and applied coherence must begin with a descriptive single-term name. Long overlooked, if known at all, and certainly never reprinted, is Knower's candidate for a name and definition of a discipline he called communicology. This article is an edited reprint to fill this 55-year void of research knowledge.